2013
DOI: 10.5935/abc.20130125
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Shocks in Patients with ICDs: Single Chamber versus Dual Chamber

Abstract: BackgroundDespite the technological evolution of the implantable defibrillator, one of the questions that remains is the possible benefit of the dual chamber versus single chamber implantable cardioverter defibrillator (ICD) in reducing inappropriate shocks.ObjectiveTo evaluate which type of device provides fewer inappropriate shocks (dual chamber versus single chamber) in patients with implantable cardioverter defibrillators (ICDs).MethodsMeta-analysis of randomized studies published in the literature compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Two meta-analyses found no superiority of dual-chamber ICDs in terms of mortality or inappropriate therapies [11,140]. Any benefit of dual-chamber discrimination is likely restricted to specific patient groups [103,138].…”
Section: Dual-chamber Vs Single-chamber Algorithmsmentioning
confidence: 99%
“…Two meta-analyses found no superiority of dual-chamber ICDs in terms of mortality or inappropriate therapies [11,140]. Any benefit of dual-chamber discrimination is likely restricted to specific patient groups [103,138].…”
Section: Dual-chamber Vs Single-chamber Algorithmsmentioning
confidence: 99%
“… 6 Additionally, a recent systematic assessment of ISs comparing dual-chamber ICDs with single-chamber devices revealed no clear superiority of dual-chamber ICDs vs. single-chamber in reducing ISs. 7 Thus, an atrial lead is not recommended for a substantial proportion of ICD-indicated patients. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials and simulated testing of induced arrhythmias that compared single- vs dual-chamber discriminators have reported inconsistent results [10] , [33] , [137] , [138] , [139] . Two meta-analyses found no superiority of dual-chamber ICDs in terms of mortality or inappropriate therapies [11] , [140] . Any benefit of dual-chamber discrimination is likely restricted to specific patient groups [103] , [138] .…”
Section: Additional Considerationsmentioning
confidence: 99%